RESPON TANAMAN CABAI RAWIT TERHADAP PEMBERIAN PUPUK ORGANIK CAIR REBUNG BAMBU - Anastesia Mebinta; Yulinda Tanari; Kamelia Dwi Jayanti (Universitas Trilogi, 2021)
Cayenne pepper is a vegetable plant that has great potential to be developed in Indonesia because it can meet the needs of households, domestic industries, exports, and raw materials in the pharmaceutical industry. One way to increase the yield of cayenne pepper is by giving liquid organic fertilizer (POC) for bamboo shoots. This study aims to determine the response of cayenne pepper toward the application of POC and gets the best POC concentration to support the growth and production of cayenne pepper. This study used a randomized block design with treatment in the form of POC concentrations consisting of 5 levels (0; 25 ml / L water; 50 ml / L water; 75 ml / L water; 100 ml / L water). Each treatment consisted of 4 replications so that there were 20 experimental units. The results show that the application of POC had a very significant effect on the number of flowers, fresh weight of fruit, and growth rate of cayenne pepper with the best treatment was 75 ml / L of water.